A leftward bias however you look at it: Revisiting the emotional chimeric face task as a tool for measuring emotion lateralization. Issue 4 (1st November 2016) - Innes, Bobby R.; Burt, D. Michael; Birch, Yan K.; Hausmann, Markus
ABSTRACT: Left hemiface biases observed within the Emotional Chimeric Face Task (ECFT) support emotional face perception models whereby all expressions are preferentially processed by the right hemisphere. However, previous research using this task has not considered that the visible midline between hemifaces might engage atypical facial emotion processing strategies in upright or inverted conditions, nor controlled for left visual field (thus right hemispheric) visuospatial attention biases. This study used novel emotional chimeric faces (blended at the midline) to examine laterality biases for all basic emotions. Left hemiface biases were demonstrated across all emotional expressions and were reduced, but not reversed, for inverted faces. The ECFT bias in upright faces was significantly increased in participants with a large attention bias. These results support the theory that left hemiface biases reflect a genuine bias in emotional face processing, and this bias can interact with attention processes similarly localized in the right hemisphere.